Sonographic Measurement of Dynamic Horizontal Instability in Acromioclavicular Joint Instability: Description of a Simple Technique and Correlation to Radiographic Parameters. (6th May 2021) - Bockmann, Benjamin; Venjakob, Arne Johannes; Thrasyvoulidis, Giorgos; Holschen, Malte; Schulte, Tobias Ludger; Nebelung, Wolfgang
Abstract : Objective: Dynamic horizontal instability is considered to be the main reason for poor outcome after treatment for acromioclavicular (AC) joint instability. In this study, we describe a simple technique to quantify this pathology via sonography. Methods: Thirty‐six shoulders from 18 patients with ac joint instabilities were examined using modified Alexander views and a standardized sonographic examination. On the Alexander views, overlap of acromion and clavicle (OLAC), glenoid center to posterior clavicle distance (GCPC), and lateral extension (LE) were measured. Afterwards, the results were analyzed and compared with sonography. Posterior translation of the clavicle and the difference of translation between healthy and injured shoulder were evaluated. Results: The mean age of the patients was 39 ± 14 years (range 19–61 years). We included 4 (22%) Rockwood type 3, 1 (6%) Rockwood type 4, and 13 (72%) Rockwood type 5 lesions. Four (22%) patients were female and 14 (78%) male patients. Posterior clavicle translation of the injured shoulder correlated strongly between OLAC and sonography ( r  = −0.514, P  = .029), and the difference of translation between healthy and injured shoulder correlated very strongly between LE and sonography ( r  = 0.737, P  < .001). Conclusion: The sonographic measurement technique for horizontal instability presented in this work could help detect horizontal instabilities. While the observation of dynamic horizontal displacement is a strength of this technique, measurements are hindered in cases of high coracoclavicular distances. Level of Evidence: Level III—retrospective cohort study. Abstract : Access the CME test here and search by article title.